Spatiotemporal Dynamics of Ambient Air Variables in a Monsoon-Influenced Agricultural Delta: Evidence from Dong Thap Province, Vietnamese Mekong Delta (2013–2024) - Ha Danh Duc; Ho Nguyen; Ho Sy Linh; Phan Van Tuan; Dang Kim Tai (Water, Air, & Soil Pollution, 2026)
Long-term, spatially explicit assessments of ambient air variables are valuable to identify hotspots, clarify meteorological controls, and guide mitigation in rapidly changing, monsoon-influenced agricultural deltas. We quantified spatiotemporal variability and potential drivers of air-quality indicators in Dong Thap Province (Vietnamese Mekong Delta) using routine monitoring data from 2013–2024 collected in two phases (26 sites in 2013–2020; 29 sites in 2021–2024). We analyzed noise, total suspended particles (TSP), CO, SO 2 , and NO 2 , together with meteorological variables, and compared three functional location types: Type I (urban areas), Type II (industrial zones), and Type III (residential, administrative, hospital, and school areas). Mean TSP and CO followed Type II > Type I > Type III, whereas SO 2 was highest in Type III and NO 2 followed Type III > Type I ≈ Type II. Across the study period, levels fluctuated markedly; noise averaged 60.0 ± 4.7 dBA and TSP averaged 180.5 ± 53.9 µg/m 3 , with occasional exceedances of permissible limits, while most observations for other parameters remained within allowable thresholds. Although the air variable values at different locations were various, seasonal analysis showed no significant rainy–dry differences for all air parameters. Inverse Distance Weighting (IDW) maps were used as descriptive spatial visualizations for each phase. Moreover, Cluster analysis was applied to analyze to group locations which had similar water values of air-quality and meteorological parameters. These findings provide a long-term baseline and transferable evidence to support air-quality management and future monitoring in Dong Thap Province.